New Florida Foliage Plant Cultivar: Aglaonema 'Stripes' - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS)
ENH-1101, a 3-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes this hybridized Aglaonema cultivar with strong bands of silvery white coloration along the lateral veins, its origin, performance, recommendations, and availability. Includes references. Published by the UF Department of Environmental Horticulture, June 2008.